2014
DOI: 10.2495/hpsm140091
|View full text |Cite
|
Sign up to set email alerts
|

Selection of conductive yarns for knitting an electrical heating element

Abstract: By the integration of electro-conductive properties in the fabric structure a flexible textile can be obtained that does not reduce the quality of comfort, maintenance and wearability of clothing. Each type of yarn has its advantages and disadvantages, for example, metal coated polymer multifilament yarn has a lower resistance to heat than metal multifilament yarn, but it is more flexible. During this research conductive knitted patterns were made and tested. For the experiments more suitable yarns for knittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Three trajectory patterns were prepared. Due to limitations in performance of spacer fabric knitting machines, and after further extended practical and theoretical knowledge, the final designs were characterised with the following features [31,32]:placement of a heating element was unidirectional,the straight trajectory of the heating element line was avoided not to limit the stretchability of the base material,the trajectory of a heating element within one design was kept in even distance in order to provide the most uniform heating,the smallest distance between heating yarns was 1 cm to avoid hotspots. Step 2. Calculating the resistance needed to obtain the estimated power of the whole mat…”
Section: Experiments Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three trajectory patterns were prepared. Due to limitations in performance of spacer fabric knitting machines, and after further extended practical and theoretical knowledge, the final designs were characterised with the following features [31,32]:placement of a heating element was unidirectional,the straight trajectory of the heating element line was avoided not to limit the stretchability of the base material,the trajectory of a heating element within one design was kept in even distance in order to provide the most uniform heating,the smallest distance between heating yarns was 1 cm to avoid hotspots. Step 2. Calculating the resistance needed to obtain the estimated power of the whole mat…”
Section: Experiments Methodsmentioning
confidence: 99%
“…Preparation of the trajectories of heating cables Three trajectory patterns were prepared. Due to limitations in performance of spacer fabric knitting machines, and after further extended practical and theoretical knowledge, the final designs were characterised with the following features [31,32]:…”
Section: Experiments Methodsmentioning
confidence: 99%
“…While finding that the maximum equilibrium temperature of the heating elements was influenced by the method of integration of conductive yarns, the authors concluded that an optimal heating element should contain conductive yarns with low electrical resistance and minor variations in electrical resistance to elongation, providing good temperature uniformity during the heating process, while being mechanically suitable for knit structure. In this work, silver-coated polyamide yarns in a three-ply configuration were able to provide the most uniform heating zones while being technically suitable for a knit structure [168]. Analysis of the method of manufacturing flexible heating fabrics by integrating a copper coil filament between two pieces of flexible interlining fabric using the thermal adhesion process, has demonstrated that reducing the copper wire spacing and the applied tension, while improving the thermal conductivity of the textile structure of the fabric, not only increases the temperature and heating rate, but also helps to maintain the fabric at a uniform temperature [169].…”
Section: Metallic Textile Heating Elementsmentioning
confidence: 98%
“…The study of the behavior of steel wire-based heating panels using single and multilayer steel wire integrated in clothes showed that the thermal effect obtained, and the time required to reach an equilibrium temperature at a fixed voltage, depended on the number of wire folds in the cloths [167]. In addition, the criteria for selecting conductive yarns for knitting an electric heater was explored using two types of steel yarn, two types of silver-coated polyamide yarn and one polyester/steel blend yarn, each of which was knit in two patterns: 1) wool/polyamide knit with a 1 m long conductive yarn in three rows of loops; 2) a conductive area in a multiply knit fabric [168]. While finding that the maximum equilibrium temperature of the heating elements was influenced by the method of integration of conductive yarns, the authors concluded that an optimal heating element should contain conductive yarns with low electrical resistance and minor variations in electrical resistance to elongation, providing good temperature uniformity during the heating process, while being mechanically suitable for knit structure.…”
Section: Metallic Textile Heating Elementsmentioning
confidence: 99%
“…We designed a textile coil by sewing the conductive thread onto the clothing. This textile coil simultaneously performs the roles of the Rx coil and thermal material [15]. The proposed wearable heater with an IPT system using a textile coil is shown in Figure 1.…”
mentioning
confidence: 99%